Faktor yang Mempengaruhi Nilai Perusahaan Properti yang Terdaftar di Indeks Saham Syariah Indonesia 2014-2017 - Devita Alliv Nurdiana; Widyan Apriliska Fajri (Telaah Bisnis, 2020)
The aim of the research is to find empirical evidence about the effect of dividend policy, capital structure, and profitability on firm value. This research uses a sample of property company that listed on Indonesian Islamic Stock Index (ISSI) from 2014-2017. We uses purposive sampling method as data collection method and Common Effect Model as an analysis technique. Using a sample of 16 property firms, we find that the dividend policy, capital structure, and profitability are positivly and significantly affect the firm value. Simultaniously dividend policy, capital structure, and profitability significantly affect the value of the company with a variation of value of 45,9 percent, while the remaining 54,1 percent is explained by other factors not explained in the research model.